Solar-powered automatic oven machine for chili and ginger drying in the highland - Adziimaa, Ahmad Fauzan; Mukti, Ilham Hary; Pramadani, Elda Yofi (Institut Teknologi Sepuluh Nopember, 2024)
Chillies and ginger are plantation crops in mountainous areas. One form of processing is by drying. The purpose of drying is to reduce the water content of plantation products. Natural drying requires the sun as a heating source with temperatures around 50˚C-60˚C, which is a problem in the mountains because the temperature is below average so it takes a long time. Natural drying has a dependence on sunlight and also a low level of hygiene. In this Research, a solar-powered Automatic Oven Machine prototype is made for chilli and ginger drying in mountainous areas. The solar-powered system as a supplier of electrical energy uses a solar panel Automatic Transfer Switch system. The selection of the title Automatic Solar Powered Oven Machine for Chilli and Ginger Dryer in Mountainous Areas aims to solve the problem of drying in mountainous areas which can cause a decrease in price and quality due to spoilage. The time used for testing this research tool is 6.53 hours, so the power required is 1506.95 Wh. The results of this study obtained the static characteristics of the temperature sensor have an accuracy of 99.21% and an error of 0.79%, while the weight sensor has an accuracy of 99.36% and an error of 0.64%. Max. overshoot at set point 50OC is 6.44% with a stedy state error of 5.46%.